Lernea cyprinacea L. (Copepoda: Caligidea) in Helostoma temmincki Cuvier & Valenciennes: the dynamics of resistance in recovered and naive fish - Woo, P. T. K.; Shariff, M. (Wiley, 1990)
All recovered and naive Helostoma temmincki lost their infections 30 days after homologous challenge with Lernaea cyprinacea. It is suggested that there is acquired protective immunity in recovered fish. No parasites were detected in five out of 20 recovered fish when the infective challenge dose was low; all naive fish (20) in the same tank were infected. In another experiment, all nine recovered fish were infected when the challenge infective dose was high. Recovered fish lost their infections (i.e. number of fish with no parasites and the number of parasites rejected) much faster than naive fish and this was very evident in the first 2 weeks after challenge. Parasites on recovered fish lost more egg sacs than naive fish during the same period. Eggs from parasites on recovered fish either did not hatch or were not infective or only caused a very low transitory infection in naive fish. It is suggested that, if no naive fish are introduced into a closed system for a period (and this has to be determined under field conditions) after an outbreak, then there will be no infective larvae in the water and the system will now be safe for restocking. This novel approach to control of the parasite L. cyprinacea and the spread of this disease will have to be carefully tested under field conditions.